2020
DOI: 10.1080/19336950.2020.1745406
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of glycan-processing genes in the dorsal root ganglia of diabetic mice and functional characterization on Cav3.2 channels

Abstract: Ca v 3.2 T-type calcium channels play an essential role in the transmission of peripheral nociception in the dorsal root ganglia (DRG) and alteration of Ca v 3.2 expression is associated with the development of peripheral painful diabetic neuropathy (PDN). Several studies have previously documented the role of glycosylation in the expression and functioning of Ca v 3.2 and suggested that altered glycosylation of the channel may contribute to the aberrant expression of the channel in diabetic conditions. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A recent GWAS reported an association with risk for cardiovascular disease [ 123 ]. In mice, Galnt16 expression was very low in the tissues tested, including brain, colon, heart, kidney, liver, lung, skeletal muscle, ovary, prostate, spleen, sublingual gland, testis, thymus and thyroid [18 (as GalNAc-Ta)], but upregulation through an unknown mechanism was observed in diabetic mice [ 124 ].…”
Section: Galnt -Associated Phenotypes In Mammalsmentioning
confidence: 99%
“…A recent GWAS reported an association with risk for cardiovascular disease [ 123 ]. In mice, Galnt16 expression was very low in the tissues tested, including brain, colon, heart, kidney, liver, lung, skeletal muscle, ovary, prostate, spleen, sublingual gland, testis, thymus and thyroid [18 (as GalNAc-Ta)], but upregulation through an unknown mechanism was observed in diabetic mice [ 124 ].…”
Section: Galnt -Associated Phenotypes In Mammalsmentioning
confidence: 99%
“…Glycosylation of T-type channels has emerged as an important post-translational modification to control the expression and functioning of the channel in the plasma membrane, and it was suggested that alteration of the glycoproteome of Ca v 3.2 may contribute to the development of peripheral pain associated with diabetes [8,10]. While several studies have previously reported the importance of canonical glycosylation sites in the expression and function of Ca v 3.2 channels [7,8,11,12], the potential role for non-canonical motifs has never been explored.…”
mentioning
confidence: 99%